2017
DOI: 10.1039/c6ra27873f
|View full text |Cite
|
Sign up to set email alerts
|

A graphene quantum dot/phthalocyanine conjugate: a synergistic catalyst for the oxygen reduction reaction

Abstract: In this work, a novel graphene quantum dot/iron phthalocyanine conjugate is synthesized. This hybrid material show efficient electrocatalytic activityviafour electron reaction and distinguished tolerance toward methanol and CO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…GQDs have recently attracted high interest as alternatives to metal-based semiconductor QDs for numerous applications, like bio-imaging [17,18] and drug delivery [19,20], light-emitting diodes [21][22][23], optoelectronic devices [24,25], electrocatalysis [26,27], or biosensors [28][29][30], due to these unique optical properties, high chemical and photo-stability, low toxicity, low cost, and easy functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…GQDs have recently attracted high interest as alternatives to metal-based semiconductor QDs for numerous applications, like bio-imaging [17,18] and drug delivery [19,20], light-emitting diodes [21][22][23], optoelectronic devices [24,25], electrocatalysis [26,27], or biosensors [28][29][30], due to these unique optical properties, high chemical and photo-stability, low toxicity, low cost, and easy functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…When smaller-sized graphene is applied, the number of active sites can be increased; however, the electrical conductivity of the conductive substrate can be deteriorated by a higher interfacial resistance originating from reduced grain size [54]. Although Koh et al reported a promising ORR composite catalyst using graphene quantum dots as a conductive supporter [53], more in-depth studies on controlling the size of graphene substrates are expected to be highly beneficial for moving the technology forward.…”
Section: Discussionmentioning
confidence: 99%
“…Koh et al prepared covalently functionalized graphene quantum dots (GQDs) with FePc using a simple ferric chloride reaction [53]. As illustrated in Figure 8Aa,b, the conjugation of GQDs with FePc in the composite was achieved by the formation of Fe-O-C bonds between them.…”
Section: Fe-o-c Linkage Between Fepc and Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…Non-noble metal based GQD catalysts also showed enhanced catalytic activity. Koh et al conjugated iron (II) phthalocyanine (FePC) with GQDs and used the catalyst for ORR in alkaline medium [72]. The catalyst also showed potential tolerance against methanol and carbon dioxide.…”
Section: Gqd Supported Metallic and Nonmetallic Nanoparticlesmentioning
confidence: 99%